2022
DOI: 10.2196/preprints.44922
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of Social Media Use Interventions on Mental Well-Being: Systematic Review (Preprint)

Abstract: BACKGROUND Problematic social media use occurs when social media interferes with a person’s daily life and mental well-being. Problematic social media use interventions, e.g., abstinence from social media, have the potential to improve users’ mental well-being. However, there is limited understanding of the effectiveness of this and other types of interventions. OBJECTIVE This systematic review… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Bringing together the latest evidence on this, a 2023 systematic review of 23 randomized controlled trials (RCTs) 15 indicated that partially or completely abstaining from social media use does appear to produce significant improvements across a range of mental health domains. Depression was the most frequently assessed outcome, with 7 out of 10 RCTs finding medium‐to‐large effects in favor of the social media withdrawal intervention.…”
Section: Psychological Impacts Of Internet Use: a Personalized Perspe...mentioning
confidence: 99%
“…Bringing together the latest evidence on this, a 2023 systematic review of 23 randomized controlled trials (RCTs) 15 indicated that partially or completely abstaining from social media use does appear to produce significant improvements across a range of mental health domains. Depression was the most frequently assessed outcome, with 7 out of 10 RCTs finding medium‐to‐large effects in favor of the social media withdrawal intervention.…”
Section: Psychological Impacts Of Internet Use: a Personalized Perspe...mentioning
confidence: 99%